Liquid-phase sintered bismuth ferrite multiferroics and their giant dielectric constant. Issue 12 (15th August 2019) - Liedienov, N.A.; Pashchenko, A.V.; Turchenko, V.A.; Sycheva, V.Ya.; Voznyak, A.V.; Kladko, V.P.; Gudimenko, A.I.; Tatarchuk, D.D.; Didenko, Y.V.; Fesych, I.V.; Makoed, I.I.; Kozakov, A.T.; et al.
Abstract: Rapid liquid-phase sintering method has been modified and used to synthesize Bi1- x La x FeO3- δ compositions (0 ≤ x ≤ 0.5). The temperature and sintering procedures to obtain stable single-phase samples have been defined. This provides a significant reduction in the synthesis time, which is especially important for mass production. Furthermore, giant dielectric constants have been observed in Bi1- x La x FeO3- δ compositions, the values of which are one order of magnitude larger than those of similar Bi-based multiferroics obtained by conventional methods. It potentially makes them one of the most promising materials for modern technological applications.